2020
DOI: 10.3390/ma13112607
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Influence of 45S5 and Cu-Containing 45S5 Bioactive Glass (BG) on the Biological Properties of Novel Polyhydroxyalkanoate (PHA)/BG Composites

Abstract: Polyhydroxyalkanoates (PHAs), due to their biodegradable and biocompatible nature and their ability to be formed in complex structures, are excellent candidates for fabricating scaffolds used in tissue engineering. By introducing inorganic compounds, such as bioactive glasses (BGs), the bioactive properties of PHAs can be further improved. In addition to their outstanding bioactivity, BGs can be additionally doped with biological ions, which in turn extend the functionality of the BG-PHA composite. Here, diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…This composition seems to lead to a disturbance of the polymeric structure. Similar results have been obtained in previous studies measuring the influence of BG concentration on the compressive strength of different polymeric matrices [34][35][36], showing that the amount of filler (here BG particles) is crucial regarding filler-hydrogel interface reactions. In accordance to the effects found on the mechanical properties, the amount of BG particles was found to play also a crucial role on the swelling capacity of the printed scaffolds.…”
Section: Discussionsupporting
confidence: 89%
“…This composition seems to lead to a disturbance of the polymeric structure. Similar results have been obtained in previous studies measuring the influence of BG concentration on the compressive strength of different polymeric matrices [34][35][36], showing that the amount of filler (here BG particles) is crucial regarding filler-hydrogel interface reactions. In accordance to the effects found on the mechanical properties, the amount of BG particles was found to play also a crucial role on the swelling capacity of the printed scaffolds.…”
Section: Discussionsupporting
confidence: 89%
“…Further evidence of the superior hemostatic activity was provided by the observation of larger platelet aggregates and a more widespread platelet pseudopodia in comparison to CX and ACS+. The polar silica framework and Ca 2+ ions in the matrix of the 1%Ga-MBG, as well as its large specific surface area, were thought to be responsible for the platelet adherence and activity on its surface [59]. The results of this study demonstrated that the number of adherent platelets on the hemostatic materials surfaces increased in number with the incubation time of up to 60 min.…”
Section: Bgs With Trace/doping Elementsmentioning
confidence: 61%
“…After 60 min of incubation, the number of adhering platelets to the surfaces of 1%Ga-MBG and CX increased, whereas the number of adherent platelets to the surface of ACS+ was not that high. Although there was no discernible difference in the quantity of adherent platelets between the 1%Ga-MBG and CX, the platelets attached to the BG were more active than in the case of CX, as seen by the lengthy pseudopodia presence [59].…”
Section: Bgs With Trace/doping Elementsmentioning
confidence: 81%
“…Selenium ions have been used for substitution in the crystal structure of HA to obtain an antibacterial ceramic material for bone tissue engineering applications [265]. The antimicrobial behaviour of Cu-ions has been evaluated by incorporating Cu-doped 45S5 BG in different short-chain length and medium-chain length PHAs scaffolds [277].…”
Section: Polyhydroxyalkanoatesmentioning
confidence: 99%